Analisis Implementasi Pelaporan Keuangan Tentang Zakat, Infak Dan Sedekah Sesuai Dengan PSAK 109 (Studi Kasus Pada Masjid Nurul Huda Desa Seletreng Kecamatan Kapongan Kabupaten Situbondo) - Siti Bariroh; Asmito Asmito (Mazinda : Jurnal Akuntansi, Keuangan, dan Bisnis, 2024)
The rise of accounting practices that are based on PSAK and have been applied to financial statements in various entities in Indonesia, both state and religious entities. However, cases of embezzlement of mosque funds allegedly triggered by the absence of accountability elements in its financial statements, which raises its own concerns for the community or parties related to the process of development and construction of mosques. This study aims to describe the application of financial statements zakat, infaq and alms in Nurul Huda mosque Seletreng, in order to know about how the form of financial statements recorded by Nurul Huda mosque, as well as analyzing the suitability of financial statements zakat, infaq and alms with PSAK 109 This descriptive qualitative research aims to describe or describe certain conditions and symptoms that occur in the Financial Statements of Nurul Huda mosque. Data collection techniques in the form of observation, interviews, and documentation. Then the data processing and analysis techniques are carried out with three stages, namely data reduction, data presentation and data verification or conclusion. The result of this study is that the financial statements of zakat, infaq and alms provided by the Nurul Huda mosque are not in accordance with those exemplified by PSAK 109 in recognition, measurement, presentation and disclosure. Because it is supposed to standardize the financial statements of zakat, infaq and alms in accordance with PSAK 109 consists of five components of financial statements, namely statements of financial position, changes in fund statements, assets under management, cash flow statements and financial statements.